Two organic–inorganic hybrid polyoxovanadates as reusable catalysts for Knoevenagel condensation. (25th March 2019) - Li, Chunxia; Zhong, Dandan; Huang, Xianqiang; Shen, Guodong; Li, Qiang; Du, Jiyuan; Li, Qianli; Wang, Suna; Li, Jikun; Dou, Jianmin
Abstract : Two novel polyoxovanadates as heterogeneous catalysts have exhibited excellent catalytic properties in the Knoevenagel condensation, especially compound1 's activity is basically maintained after three cycles. Abstract : Two novel organic–inorganic hybrid polyoxovanadates, i.e., [Ni(1-mIM)4 (H2 O)2 ][Ni(H2 O)5 ]2 V10 O28 ·5.5H2 O (compound1 ) and [V(O)(1-vIM)4 ]2 V4 O12 ·H2 O (compound2 ) (1-mIM = 1-methylimidazole; 1-vIM = 1-vinylimidazole) were synthesized under routine conditions. The two polyoxovanadate hybrids were further unequivocally characterized by the usual physicochemical techniques such as single crystal X-ray diffraction (SCXRD), Fourier transform infrared spectroscopy (FT-IR), powder X-ray diffraction (PXRD), thermogravimetric (TG) analyses and elemental analyses. The SCXRD analyses demonstrated that the three Ni 2+ atoms of compound1 presented distorted octahedral geometry; one of the three Ni 2+ atoms coordinated with four 1-mIM molecules and two coordinated water molecules, thereby exhibiting a [NiN4 O2 ] binding set. Furthermore, the other two Ni 2+ atoms were coordinated with five water molecules and one decavanadate polyanion, presenting an [NiO6 ] coordination environment. The structure of2 exhibited a central [V4 O12 ] 4− unit attached to the opposite sides of two [V(O)(1-vIM)4 ]2 groups, in which the V center displayed distorted octahedral configuration. More importantly, the two organic–inorganic hybrid polyoxovanadates were further studied using the Knoevenagel condensation reaction, and they were found to display efficient heterogeneous catalytic activities (yield up to 99%). The catalytic performance of compound1 did not decrease even after three runs of catalytic cycling.